Use of Technology in Open and Distance Learning: Transforming Education - Ferdinand Salomo Leuwpl; Gogor Chrismass Setyawan; Agus Riyadi; Ardian Al Hidayat; Dedi Gunawan Saputra (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
A long with the times, the world of education is also developing. Technology has a very large influence in the world of education. Where technology is an important part of education. With the existence of technology, changes in the world of education are getting better day by day. This educational progress cannot be separated from the role of technology in increasing learning innovation in the education system. For this reason, technology is used as a means to create learning innovations in the current education transformation. The purpose of this research was to find out the use of technology in distance and open learning: educational transformation. The method used in this research is a quantitative research method with a research design in the form of a survey. The data in this study were obtained by filling out a questionnaire on the Google form link. The results of this study are that the Use of Technology in Distance and Open Learning: Educational Transformation, provides unique and interesting learning through the use of various technologies in the learning process. The conclusion from this study is that the use of technology in distance and open learning is very influential and suitable to be used to support distance and open learning as a change in the world of education or educational transformation, because students can learn anywhere and anytime even from home and the educational process is also supported. by the technology used. This research is also an answer from people who experience many obstacles in the educational process related to the time and place of education implementation. The limitation in this research is that researchers only conduct research at the school level. The researcher also hopes that further researchers will expand research to a higher level and the researcher also hopes that in the future other researchers will emerge who can develop this research and focus on one part of technology.